Kebijakan Kriminal Perburuan Burung Wallacea Di Kepulauan Aru - Yanti Amelia Lewerissa (Faculty of Law, Universitas Pattimura, 2021)
Hunting for birds in the Aru Islands as one of the Wallacea regions is a crime that must be overcome to prevent the destruction of Wallacea bird species in Indonesia. This study aims to analyze how the criminal policy of hunting Wallacea birds in the Aru Islands. The research method used is normative jurudic, i.e. analyzing library materials or searching documents related to the problem under study. The approach used is the statutory approach and conceptual approach. Source of data used are secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. Data collection methods are the study of literature and analyzed qualitatively. The results showed that hunting birds on the Aru Islands if left unchecked would threaten Wallacea bird species. Efforts to control the crime of bird hunting can be done by using means of punishment and non-punishment. Non-penal means that can be applied through the application of Sasi Cenderawasi and Sasi Walet as a form of local wisdom of the Aru people in maintaining the balance of nature in which they live. While the means of punishment through the application of legislation relating to hunting animals (birds). It is hoped that the Government can add forest police personnel or Nature Conservation Center officers, improve facilities / infrastructure as support activities for the protection and supervision of the nature reserve area. In addition, community participation must be increased through awareness to obey the Sasi rules as local wisdom.